Control of White-Opaque Phenotypic Switching in Candida albicans by the Efg1p Morphogenetic Regulator - Sonneborn, Anja (American Society for Microbiology, 1999)
Phenotypic switching in Candida albicans spontaneously generates different cellular morphologies and is manifested in strain WO-1 by the reversible switching between the white and opaque phenotypes. We present evidence that phenotypic switching is regulated by the Efg1 protein, which is known as an essential element of hyphal development (dimorphism). Firstly, EFG1 is expressed specifically in cells of the white but not the opaque phenotype. During mass conversion from the opaque to the white phenotype, the EFG1 transcript level correlates with competence of switching of opaque cells to the white form. Secondly, overexpression of EFG1 by a PCK1p-EFG1 fusion forces opaque-phase cells to switch to the white form with a high level of efficiency. Thirdly, low-level expression of EFG1 in strain CAI-8 generates a cellular phenotype similar to that of opaque cells in that cells bud as short rods, which cannot be induced to form hyphae in standard conditions; such cells (unlike authentic opaque cells) lack typical surface “pimples.” Importantly, the opaque-specific OP4 transcript is induced in the opaque-like cells generated by strain CAI8 as a response to low-level expression of EFG1. The results suggest that high EFG1 expression levels induce and maintain the white cell form while low EFG1 expression levels induce and maintain the opaque cell form. It is proposed that changes in EFG1 expression determine or contribute to phenotypic switching events in C. albicans.